2002
DOI: 10.1086/340316
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Linkage Analysis of Quantitative Spirometric Phenotypes in Severe Early-Onset Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a common, complex disease associated with substantial morbidity and mortality. COPD is defined by irreversible airflow obstruction; airflow obstruction is typically determined by reductions in quantitative spirometric indices, including forced expiratory volume at 1 s (FEV(1)) and the ratio of FEV(1) to forced vital capacity (FVC). To identify genetic determinants of quantitative spirometric phenotypes, an autosomal 10-cM genomewide scan of short tandem repeat (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
1
8

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 34 publications
14
138
1
8
Order By: Relevance
“…Furthermore, in recent genomewide scans for COPD, the MBL2 gene locus (10q11) was not among chromosomal regions strongly linked to lung function measurements in middle-aged individuals of the Framingham cohort 22 or families with severe, earlyonset COPD probands. 23 On the other hand, this does not entirely exclude a role for MBL2 in the development of COPD later in life, as is more commonly seen clinically. We have not excluded the possibility that the rare B/B genotype could still be associated with COPD susceptibility, due to greater impairment of host defence, in which case a much larger sample size than ours would be required, and primers that avoid the potential misclassification of A/B and B/B individuals should be employed.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, in recent genomewide scans for COPD, the MBL2 gene locus (10q11) was not among chromosomal regions strongly linked to lung function measurements in middle-aged individuals of the Framingham cohort 22 or families with severe, earlyonset COPD probands. 23 On the other hand, this does not entirely exclude a role for MBL2 in the development of COPD later in life, as is more commonly seen clinically. We have not excluded the possibility that the rare B/B genotype could still be associated with COPD susceptibility, due to greater impairment of host defence, in which case a much larger sample size than ours would be required, and primers that avoid the potential misclassification of A/B and B/B individuals should be employed.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the patients with liver diseases had a significantly higher prevalence of COPD when the odds ratio was adjusted by the amount of smoking and age. (18,19), lung growth (20), gender (21,22), socioeconomic status (23) and nutrition (24). Furthermore, recently, it has been reported that systemic inflammation could be involved in the pathogenesis of COPD (5)(6)(7), and that COPD patients are at increased risk for several comorbidities including myocardial infarction, osteoporosis, depression and diabetes (1).…”
Section: F I G U R E 3 T H E P R E V a L E N C E O F Cop D A C C O mentioning
confidence: 99%
“…Since FEV1 (% pred) was studied in only four asthma genome screens, linkage scans conducted for lung function phenotypes in families with early-onset chronic obstructive pulmonary disease (COPD) and from the general population were considered [24]. Among the three linkage signals detected for FEV1, 1p36 was reported to be linked to asthma in two scans [22,25] and 6q14 to eosinophils in one scan [26], whereas linkage to 2q36 was observed for atopy phenotypes in two asthma scans [18,21,22] and for lung function phenotypes in asthmatic families [19] and early-onset COPD families [27,28]. Regarding this latter result, longitudinal studies have shown that asthma is associated with accelerated lung function decline and is a risk factor for COPD [29].…”
Section: Phenotype Definition and Linkage Analysis Outcomesmentioning
confidence: 99%